Dakwah Di Era Digital: Studi Kasus Dakwah Melalui Facebook Dengan Metodologi Analisis Konten - SULANJANI, ANDI (LPPM Sekolah Tinggi Teknologi Cipasung, 2025)
The development of digital technology has brought significant changes to communication patterns, including the dissemination of Islamic da’wah. Social media, particularly Facebook, has become a strategic medium for distributing religious messages. This study aims to analyze da’wah content disseminated through the Facebook platform and to evaluate the forms, characteristics, and effectiveness of digital da’wah messages. Using a qualitative approach with content analysis methods, this research examines several popular da’wah accounts on Facebook over a three-month period. The findings indicate that digital da’wah on Facebook employs short narratives, appealing visuals, and thematic approaches relevant to contemporary issues. Although digital da’wah expands audience reach, challenges related to content validity and public response remain key concerns. This study recommends strengthening digital da’wah literacy to enhance the effectiveness of Islamic da’wah in the digital era.